Environmental education and digital pedagogy: an analysis of the regulatory framework - Tolochko, Svitlana; Bordіug Nataliia (ScienceRise: Pedagogical Education, 2026)
The article is devoted to the presentation of the results of the analysis and justification of the regulatory framework for environmental education and digital pedagogy, the need to integrate the potential of both branches for the formation of environmental competence, worldview, consciousness, and culture of education seekers. The current state of development of the regulatory framework related to the organization and implementation of environmental education was analyzed, in particular, the Law of Ukraine "On Education", the Concept of Environmental Education of Ukraine, the Concept of National-Patriotic Education in the Education System of Ukraine, the National Program for the Education of Children and Students in Ukraine, the National Doctrine for the Development of Education of Ukraine, the Concept of the New Ukrainian School. The current regulatory documentation related to digital pedagogy was considered: the Laws of Ukraine "On Digital Content and Digital Services", "On the National Program of Informatization", the Resolution of the Cabinet of Ministers of Ukraine "On Approval of the Concept of the Development of Digital Competencies and Approval of the Action Plan for Its Implementation", "Some Issues of Digital Transformation". The feasibility of implementing the capabilities of digital pedagogy in environmental education is substantiated on the basis of the analysis of documents and thesaurus relevant in the context of the research being carried out. The feasibility of using digital technologies (audio and visual in real time, using text messages, online text, audio and video chats, e-mail, communication and discussion forums, etc.) is confirmed. The impact on the development of digital content of education in general and environmental education in particular by augmented and virtual reality, artificial intelligence, robotics, media education, gamification, STEM / STEAM education is demonstrated. Recommendations are proposed for the implementation of digital technologies in environmental education, in particular digital educational platforms ("All-Ukrainian School Online", "Action. Education for All", "EcoEducation", "Education for Life", "EcoSystem", "Ecoaction"). The possibility for students and teachers to use the information provided in free access on the specified platforms for writing scientific papers or implementing environmental projects has been confirmed